Hodnocení zánětlivé celulizace (tumor infiltrujících lymfocytů) u solidních nádorů - Dundr, P; Němejcová, K; Bártů, M; Matěj, R; Rohan, Z; Tichá, I (Klinicka onkologie, 2017)
BACKGROUND: The tumor microenvironment plays an important role in tumorigenesis and the tumor-host relationship. An important part of the tumor microenvironment is inflammatory infiltration. Its evaluation in solid tumors has prognostic meaning and appears also to be predictive of outcome, which is particularly important for predicting responses to immune checkpoint inhibitors. However, the methodology used to assess inflammatory infiltration is problematic, because it has been standardized only for certain types of tumors. OBJECTIVE: The present study provides an overview of current issues related to the evaluation of inflammatory cells (tumor infiltrating lymphocytes) in solid tumors, specifically in tumors of the breast, lung, head and neck, gastrointestinal tract, female genital tract, urogenital tract, brain, malignant mesothelioma, and malignant melanoma. Various methodologies for evaluation are mentioned, including the efforts that are being made to standardize these methodologies and the importance of immunophenotyping inflammatory infiltrates. With regard to clinical meaning, prognostic and predictive significance are also discussed. CONCLUSION: The evaluation of TILs in solid tumors often has predictive value; however, the results have been equivocal. There is also ambiguity about the predictive use of this marker. Despite all the methodological developments, which have resulted in the implementation of complicated technologies (image analysis, multiplex fluorescence immunohistochemistry, and mass spectrometry) for the evaluation of the various aspects of inflammatory infiltrates present in tumors, including their functional characteristics, there is still a need for standardization and development of inexpensive and universally available methodologies to enable the wide use of TIL evaluations in clinical settings. The recently proposed unified methodology may be used in all solid tumors and could help resolve one of the main limitations of the routine use of TIL, i.e., the inconsistent approach to assessment.Key words: solid tumors - tumor-infiltratig lymphocytes - inflammatory cells This work was supported by program of the Czech Ministry of Health No. RVO-VFN 64165 and AZV project No. 16-30954A, Charles University and OPPK (CZ.2.16/3.1.00/24509). The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 24. 9. 2017Accepted: 3. 10. 2017.
Keywords: nádory; lidé; Neoplasms; tumor infiltrující lymfocyty; Lymphocytes, Tumor-Infiltrating; Humans